Lewis acid-mediated controlled anionic polymerization at high temperature - Bornhoft, Laura O'Neill, author; Chen, Eugene Y.-X., advisor; Shores, Matthew P., committee member; Kipper, Matthew J., committee member (Colorado State University. Libraries, 2011)
Lewis acid-mediated controlled anionic polymerization under industrially desired conditions (ambient or higher temperature) is described in this thesis. The central theme focuses on the utilization of Lewis acids, primarily trialkylaluminum tris(pentafluorophenyl)alane and isoelectronic silylium cation, in three different anionic polymerization systems to mediate, or act as catalyst, for the controlled anionic polymerization of (meth)acrylic monomers or the anionic coordination ring opening polymerization of bio-derived cyclic monomers ɛ-caprolactone and meso-lactide. The first system uses potassium hydride as an anionic initiator, activated with aluminum Lewis acids of varied acidity, sterics and equivalents, for the controlled polymerization of methyl methacrylate (MMA) and block copolymerization of MMA with other alkyl methacrylates such as n-butyl methacrylate and 2-ethylhexyl methacrylate. The second system involves the synthesis of nonpolar-polar block copolymer of poly(styrene-b-methacrylate) in aliphatic solvents at high temperature. Aluminum Lewis acids or non-polymerizable monomers such as N,N-dimethyl methacrylamide are added between blocks to control the propagation crossover from the styrenic block to the methacrylate block. The third system utilizes silylium ions to catalyze anionic polymerization, focusing on the anionic coordination polymerization of cyclic esters and the development of new dinuclear catalysts exhibiting potential to new polymerization pathways that could promote faster polymerization under dilute conditions and enhanced polymerization stereochemical control.